Oral ketamine vs placebo in patients with cancer-related neuropathic pain - Fallon, Marie T.; Wilcock, Andrew; Kelly, Caroline A.; Paul, James; Lewsley, Liz-Anne; Norrie, John; Laird, Barry J. A. (American Medical Association, 2018)
Ketamine hydrochloride is used as an adjuvant treatment for cancer-related neuropathic pain, but evidence of its effectiveness is limited.1 Findings of a large trial investigating the use of ketamine for general cancer pain were negative, but the population studied did not specifically have neuropathic pain. A randomized trial of oral ketamine for cancer-related neuropathic pain has been called for, and the present trial addresses that need.